Temperature dynamics and mechanical properties analysis of carbon fiber epoxy composites radiated by nuclear explosion simulated light source - Lin Yuan; Jun Li; Boyu Wang; Xin Zhang; Weijie Zhu; Yang Liu; Haiyang Zhang; Xiaoxiang Han (Scientific Reports)
Abstract The impact of light radiation, a predominant energy release mechanism in nuclear explosions, on material properties is of critical importance. This investigation employed an artificial light source to replicate the effects of nuclear explosion radiation and utilized a physical information neural network (PINN) to examine the temperature evolution and corresponding changes in the mechanical properties of carbon fiber/epoxy composites (CFEC). A light source simulating nuclear explosion’s light radiation was built to irradiate the CFEC, then measure the reflection spectrum and temperature of samples. A heat conduction model was developed, and the temperature dynamics were obtained through the integration of PINN with experimental data. Post-irradiation testing indicated significant modifications to the sample properties, with the thermal and photochemical effects of the simulated radiation leading to a decrease in reflectance across multiple wavelengths. This resulted in different reductions in tensile strength (1.64%), compressive strength (17.35%), interlamellar shear strength (ILSS) (0.51%), and post-impact compressive strength (2.77%). The insights gained from this comprehensive analysis are essential for the rapid prediction of temperature changes and the formulation of robust light radiation protection strategies for equipment exposed to nuclear explosion environments.